Respuestas

2013-04-29T01:55:22+02:00

A.   12+7x-1+3x=7

              7x+3x   =7-12+1

                     10x=-4

                         x=-4/10

                        x=-2/5

 

B     6x+8x=10+48

              14x=58

                 x=58/14

                 x=29/7

 

Debes pasar las x a un lado y lo términos independientes al otro, y luego simplificas 

 

Espero te sirva :)

 

  • Usuario de Brainly
2013-04-29T01:57:26+02:00

 A- 12+7.x-1+3.x=7

 

12+7x-1+3x=7

12+10x=7+1

10x=8-12

x=-4/10

x=-2/5

 

 

 

B- 6.x+8.x=10+48

 

6x+8x=10+48

14x=58

x=58/14

x=29/7